2019
DOI: 10.1371/journal.pone.0221930
|View full text |Cite
|
Sign up to set email alerts
|

High production of carotenoids by the green microalga Asterarcys quadricellulare PUMCC 5.1.1 under optimized culture conditions

Abstract: Since carotenoids are important as natural colorants, antioxidants, neutraceutics and pharmaceutics, the aim of the present study was to find a new good source of these pigments. We hereby report a green microalga Asterarcys quadricellulare PUMCC 5.1.1 as a new and good producer of carotenoids. The organism produced 35±1.75 μg carotenoids mg −1 dry biomass during stationary phase in control cultures. The growth and carotenoids production by the test microalga were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 69 publications
4
32
0
2
Order By: Relevance
“…Coelastrum sp. and Asterarcys quadricellulare have nutrition and pharmaceutical potential 41 , 42 . Parachlorella beijerinckii is currently employed in the cosmetics industry 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Coelastrum sp. and Asterarcys quadricellulare have nutrition and pharmaceutical potential 41 , 42 . Parachlorella beijerinckii is currently employed in the cosmetics industry 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A continuous search for potential new strains for large-scale production of these pigments are still advancing as the current major strains are still limited to a few species, namely, Spirulina platensis, Haematococcus pluvialis and Chlorella sp. Singh et al [ 136 ] discovered Asterarcys quadricellulare PUMCC 5.1.1 strain, a green microalga with a promising characteristic for carotenoid production while Kaushal et al [ 137 ] reported a new cyanobacterium Nodularia sphaerocarpa PUPCCC 420.1 which produces phycobiliprotein and reckoned as a good candidate for production at commercial scale.…”
Section: Microalgae In Nutraceuticals/foodmentioning
confidence: 99%
“…Diverse agro-industrial wastes have been investigated for production of the well-known Monascus pigments (Table 1), and some processes using such inexpensive substrates presented high pigment yields (Embaby et al, 2018). In addition, industrial wastewaters are successfully used for production of phycocyanins and carotenoid pigments by microalgae (Singh et al, 2019;Arashiro et al, 2020). Intracellular carotenoids (β-carotene, γ-carotene, torulene, and torularhodin) from Rhodotorula species have been produced by using different agro-industrial byproducts as sugarcane bagasse, wheat bran, rice bran, silage, whey, raw glycerol, corn steep liquor, sugarcane molasses, waste chicken feathers, fruit waste extract, and many others (Sharma and Ghoshal, 2019;Korumilli et al, 2020).…”
Section: Microbial Pigment Production Using Agro-industrial Byproductsmentioning
confidence: 99%